ACTIVITIES TO INCREASE THE EFFICIENCY OF PERIODICALS ARTIFICIAL WELLS - Alena Olegovna Shesteren (Наука. Инновации. Технологии)
Introduction: urgency of this work lies in the need to solve problems of gas-lift optimization in regime of minimum specific gas consumption for oil and gas industry. Optimization of gaslift wells operation and redistribution of injected gas allow more rational use of gas resources and significantly increase production at fields of JV «Vietsovpetro». parameters of operation for artificial gas-lift wells, a list of complications in operation of low-yield wells were used. Materials and Methods: Results: the design features of well that influence operation of artificial gas-lift are determined. A number of faults in gas-lift operation are revealed. The methods for increasing efficiency of gas-lift are substantiated. Discussion and Conclusion: the author analyzed causes of the malfunction in gas-lift operation, proposed measures to eliminate them. The analysis of measures to increase the efficiency of gas-lift wells was carried out.